Moldova Financial Sector Assessment Program : Technical Notes - World Bank (World Bank, Washington, DC, 2021)
Moldova declared its independence in August 1991 and adopted its current constitution in July 1994. Over the intervening decade, the legal framework governing the regulation and supervision of the country's financial and business sectors has undergone significant reform. However, Moldova has lagged behind in the creation of a business-friendly legal and tax environment. Recent reports and surveys have confirmed that the risks and costs of doing business are high and that administrative burdens of all kinds are excessive. Access to finance is limited and regulatory compliance costs are amongst the highest in the region. Moldova might wish to emulate the practice of India, for example, where the authorities have sought to address this issue by requiring inspection officials to complete a logbook at the premises of the company undergoing inspection, explaining why they are inspecting and summarizing their findings. To their credit, the Moldovan authorities have recognized many of the major areas in need of review and restructuring and have embarked upon an ambitious legal reform agenda.